To Assess the Outcome of Temporo-Mandibular Joint Arthrocentesis in the Treatment of Internal De-Arrangement of Temporo-Mandibular Joint - Shoaib Zuberi, Asad Iqbal, Ammar Azim Khan Niazi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The two joints connecting the jawbone to the skull are called the temporomandibular joints. The TMJs are another name for these joints (TMJ). It's a connection between the mandible (at the bottom of the skull) and the temporal bone (at the top of the skull). Internal derangement of the temporomandibular joint (TMJ) is a condition in which the disc in the TMJ is displaced out of its normal functional relationship with the mandibular condyle and the articular region of the temporal bone. The problem is within the TMJ, where it can cause serious problems. Pain from an internal condition can be effectively treated with arthrocentesis, or AC (ID). Objectives: The purpose of this study is to evaluate the effectiveness of arthrocentesis of the temporomandibular joint in the management of temporomandibular joint internal derangement. Study Design: Descriptive case series. Setting: Department of Oral and Maxillofacial Surgery, Mayo Hospital, Lahore. Duration of Study: Six months after approval of synopsis i.e. 22-12-2018 to 22-06-2019 Methodology: 60 Patients matched the inclusion criteria selected from OPD of department of Oral and Maxillofacial Surgery, Mayo hospital Lahore. Informed consent was obtained. Demographic details also obtained. Patients were undergone surgery by senior consultant under LA. After surgery, patients were shifted in post-surgical wards and discharged from there after 48 hours. Patients were advised to present after 1 week of surgery in OPD. After 1 week, patients were evaluated for postoperative maximal mouth opening. Patients were also asked for presence of postoperative pain by using VAS and score was noted (as per operational definition) by researcher himself. All this information was recorded through proforma (attached). Results: Total of 60 patients, 46.7 % ( n=28) were male and 53.3 %( n=32) were female, Mean age of patients was 37.38±15.11. Sixty percent, or n=36, of the patients were found to be between the ages of 18 and 35, and forty percent, or n=24, were found to be between the ages of 36 and 60. Mean duration of TMJ Internal derangement was 49.86±19.12. Mean maximal mouth opening was 35.55±3.51mm. (p-value 0.001) and mean post-operative pain was 2.23± 1.06. (P-value 0.001). Practical Implication: This study will help to understand the effectiveness of arthrocentesis of the temporomandibular joint in the management of temporomandibular joint internal derangement Conclusion: Finally, we decided that arthrocentesis is a straightforward, minimally invasive treatment. Internally dislocated temporomandibular joints (TMJ) can be corrected with this method. For those who have closed-lock internal derangement, TMJ arthrocentesis appears to be a risk-free alternative with a reduced potential for consequences. Keywords: Temporomandibular Joint, Arthrocentesis, Post-operative Pain, Derangement, Arthrocentesis, Arthroscopy.